IMPLEMENTATION OF LAW NO. 33 OF 2014 CONCERNING HALAL PRODUCT GUARANTEES AT WATER DEPOTS (CASE STUDY IN PADANG BULAN SELAYANG I VILLAGE) - Fahrul Raji Khassa; Cahaya Permata (QANUN: Journal of Islamic Laws and Studies, 2026)
Law No. 33 of 2014 concerning Halal Product Guarantee requires mass-produced products to be halal certified. Refillable drinking water products in Padang Bulan Selayang I Village do not have adequate halal certification and labeling. This study aims to determine the regulations regarding halal certification requirements for water depots and the implementation of halal certification at water depots in Padang Bulan Selayang I Village. This study is an empirical legal study using a living case studies and statute approach. Data were collected through interviews and document studies, then processed and analyzed qualitatively. The results of this study show that, of the ten business actors interviewed, not a single water depot in Padang Bulan Selayang I Village has been halal certified, even though, as mandated by Article 4 of the Halal Product Guarantee Law, water depots are among those that are required to have halal certification. This shows that the legal awareness of water depot business actors in Padang Bulan Selayang I Village is still low and not in line with Law Number 33 of 2014 concerning Halal Product Guarantee.